A survey of library school faculty in the Philippines - Montes, Angelita L.; Vallejo, Rosa M.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1984)
This survey was conducted to draw a profile of library science teachers throughout the country in terms of their personal characteristics, academic background and experience, workload, teaching methods, research output, membership in associations and expressed needs and concerns.
The normative survey method was used with the questionnaire as the basic instrument. The questionnaire carried eight major headings as follows: educational preparation; profesional and teaching experience; instructional methodology; teaching pay; continuing education; membership in various organizations; research output and current and pressing problems. A total of 115 questionnaires was sent but only 74 or 64.3 percent was returned.
The findings revealed that the library science faculty is predominantly female, between 31-40 years of age, married and works on a part-time basis. They are academically qualified to teach L.S. since 50 percent have master's degrees library science as major field of specialization. For their bachelor's degrees, 50 percent have library science as their area of specialization. Although their previous professional experience is varied, most of them have been librarians since they started their career. Their level of education affects their present position in the same manner as the length of their teaching experience has an influence on rank and rank on salaries yet the findings indicate that the library educators generally receive salaries not commensurate to their rank/position.
The full-time faculty members devote most of their time in teaching while library administration is largely occupied by the part-timers. As far as course preference is concerned, Library Administration topped the list followed by Reference and Readers' Services. Preference is precisely due to interest and field of specialization and not necessarily due to work experience.
The group manifested a keen interest in attending meetings, conferences and workshops as well as in affiliating with professional associations. Research is a neglected function among this group; the deterrent factor is time. Majority are part-time librarians concentrating their time on library work and teaching after office hours.
The library educators' most common problem was the dearth and at the same time the high cost of instructional materials. Other problems consist of those with the students, the administration and the need of technical expertise in that order.
From the above findings, the researcher and the respondents share some recommendations. Quality library educators who are on full-time basis need to be recruited. To attract them, scholarships for faculty development and opportunities for sabbatical leaves should be offered. School administrators need to look into policies for promotion as well as those on fringe benefits. Library associations, the Philippine Association of Teachers of Library Science (PATLS) in particular, must take the lead in boosting the morale of the library profession by pushing through the professionalization bill. The library educators themselves and PATLS have to join hands in upgrading the library profession.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library schools -- Philippines -- Faculty